2021
DOI: 10.3390/polym14010031
|View full text |Cite
|
Sign up to set email alerts
|

Potentiodynamic Electrochemical Impedance Spectroscopy of Polyaniline-Modified Pencil Graphite Electrodes for Selective Detection of Biochemical Trace Elements

Abstract: In this study, we analyzed the application of potentiodynamic electrochemical impedance spectroscopy (PDEIS) for a selective in situ recognition of biological trace elements, i.e., Cr (III), Cu (II), and Fe (III). The electrochemical sensor was developed using the electropolymerization of aniline (Ani) on the surface of the homemade pencil graphite electrodes (PGE) using cyclic voltammetry (CV). The film was overoxidized to diminish the background current. A wide range of potential (V = −0.2 V to 1.0 V) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The processes arising from the Fe 2+ / 3+ redox probe at the electrode interface are presented with the Randles equivalent circuit as a capacitor in parallel with a series of a resistor for a charge transfer resistivity and a Warburg impedance element (C|(Rct-W); labeled IV). The charge transfer resistance for oxidation of Fe 2+ to Fe 3+ in the absence of bacteria was found to be 650 Ω which agrees with previously reported values. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The processes arising from the Fe 2+ / 3+ redox probe at the electrode interface are presented with the Randles equivalent circuit as a capacitor in parallel with a series of a resistor for a charge transfer resistivity and a Warburg impedance element (C|(Rct-W); labeled IV). The charge transfer resistance for oxidation of Fe 2+ to Fe 3+ in the absence of bacteria was found to be 650 Ω which agrees with previously reported values. , …”
Section: Resultssupporting
confidence: 91%
“…The charge transfer resistance for oxidation of Fe 2+ to Fe 3+ in the absence of bacteria was found to be 650 Ω which agrees with previously reported values. 32 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…While all individual measurements were conducted at 1000 Hz, it was observed that in the SCFA mixture more robust results could be obtained at the frequency of 100 Hz. The imaginary component of impedance ( Z ” ) at 100 Hz is reported instead of Z ’ as the response is directly associated with the charge transfer resistance [27] and Z ” maintained a linear relationship with different acid concentrations, indicating its utility in converting the sensor measurements to SCFA concentrations in mixture conditions. For example, the descending value of Z ” ( Figure S7a-b ) for the impedance changes of acetic acid at the concentration of 10 mg/ml and 0.5 mg/ml of propionic acid and butyric acid and the increasing value of Z ” for propionic acid in the mixture ( Figure S7c-d ) revealed the same trend as it was observed in the MM and pure electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 13, 2022. ; https://doi.org/10.1101/2022.09.11.507374 doi: bioRxiv preprint that allow real time detection, electrochemical sensors, and more specifically chemiresistors, provide extremely high selectivity [27]. They also come with other benefits such as ease of fabrication and miniaturization, small footprint, high stability and high temporal-spatial resolution, which are all important for real-time monitoring of biochemical molecules [27]. Chemiresistors are made up of a conductive thin-film sensing layer sandwiched by a pair of electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation